3(2y+4)-3y=6(y+1)

Simple and best practice solution for 3(2y+4)-3y=6(y+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2y+4)-3y=6(y+1) equation:


Simplifying
3(2y + 4) + -3y = 6(y + 1)

Reorder the terms:
3(4 + 2y) + -3y = 6(y + 1)
(4 * 3 + 2y * 3) + -3y = 6(y + 1)
(12 + 6y) + -3y = 6(y + 1)

Combine like terms: 6y + -3y = 3y
12 + 3y = 6(y + 1)

Reorder the terms:
12 + 3y = 6(1 + y)
12 + 3y = (1 * 6 + y * 6)
12 + 3y = (6 + 6y)

Solving
12 + 3y = 6 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
12 + 3y + -6y = 6 + 6y + -6y

Combine like terms: 3y + -6y = -3y
12 + -3y = 6 + 6y + -6y

Combine like terms: 6y + -6y = 0
12 + -3y = 6 + 0
12 + -3y = 6

Add '-12' to each side of the equation.
12 + -12 + -3y = 6 + -12

Combine like terms: 12 + -12 = 0
0 + -3y = 6 + -12
-3y = 6 + -12

Combine like terms: 6 + -12 = -6
-3y = -6

Divide each side by '-3'.
y = 2

Simplifying
y = 2

See similar equations:

| 4x-2=8x+3 | | b^2-6m-27=0 | | 3x-1-4x=2x-3 | | 4(-5y+1)=-3(y+6) | | 9x-2x=49 | | 4y-9x=20xy | | (4r^3)(3rs)=0 | | -15=5(3q-10q)-5q | | 7(x+10)+2x+120=180 | | 6x^3-2x^2=0 | | 3x+8=5x-4 | | 57+x+65=90 | | 9u-2u=56 | | 6x+14=4x-20 | | 4x/5=-2 | | v+(v-33.1)+(v+26.2)=194.4 | | 12+8x-x^2=0 | | x+3+5=38 | | 3x-20+68=180 | | 5x+8-12x=-6x-3 | | x^2=2(x+112) | | 3.5b-3.34=75.1 | | 4s=3s-14 | | 7(4-2x)-6x=-32 | | 15x^3+26x^2+8x=0 | | p(5p-8)=0 | | 6p+1=3(2p-5) | | 7(4-2x)-6x= | | -(16c-53d+14)= | | 8u+2(u-10)=10 | | 7y+2(y-8)=4(y+2)-3 | | X+10+3x=170 |

Equations solver categories